ALMA Band 6 high-resolution observations of the transitional disk around SY Chamaeleontis. (22nd February 2023) - Orihara, Ryuta; Momose, Munetake; Muto, Takayuki; Hashimoto, Jun; Liu, Hauyu Baobab; Tsukagoshi, Takashi; Kudo, Tomoyuki; Takahashi, Sanemichi; Yang, Yi; Hasegawa, Yasuhiro; Dong, Ruobing; Konishi, Mihoko; et al.
Abstract: In this study, we reported the results of high-resolution (${0{^{′ ′}_{.}}14}$ ) Atacama Large Millimeter/submillimeter Array (ALMA) observations of the 225 GHz dust continuum and CO molecular emission lines from the transitional disk around SY Cha. Our high-resolution observations clearly revealed the inner cavity and the central point source for the first time. The radial profile of the ring can be approximated by a bright narrow ring superimposed on a fainter wide ring. Furthermore, we found that there is a weak azimuthal asymmetry in dust continuum emission. For gas emissions, we detected 12 CO(2–1), 13 CO(2–1), and C 18 O(2–1), from which we estimated the total gas mass of the disk to be 2.2 × 10 −4 M ⊙ , assuming a CO/H2 ratio of 10 −4 . The observations showed that the gas is present inside the dust cavity. The analysis of the velocity structure of the 12 CO(2–1) emission line revealed that the velocity is distorted at the location of the dust inner disk, which may be owing to a warping of the disk or radial gas flow within the cavity of the dust disk. High-resolution observations of SY Cha showed that this system is composed of a ring and a distorted inner disk, which may be common, as indicated by the survey of transitional disk systems at a resolution of ${\sim}{0{^{′ ′}_{.}}1}$ .